Availability of PEth testing is associated with reduced eligibility for liver transplant among patients with alcohol‐related liver disease. Issue 5 (27th January 2022) - Selim, Ranya; Zhou, Yueren; Rupp, Loralee B.; Trudeau, Sheri; Naffouj, Sandra; Shamaa, Omar; Ahmed, Abdelwahab; Jafri, Syed‐Mohammed; Gordon, Stuart C.; Segal, Antu; Gonzalez, Humberto C.
Abstract: Background: Serum phosphatidylethanol (PEth) is a highly sensitive test to detect alcohol use. We evaluated whether the availability of PEth testing impacted rates of liver transplant evaluation terminations and delistings. Methods: Medical record data were collected for patients who initiated transplant evaluation due to alcohol‐related liver disease in the pre‐PEth (2017) or PEth (2019) eras. Inverse probability weighting (IPW) was used to balance baseline patient characteristics. Outcomes included termination of evaluation or delisting due to alcohol use; patients were censored at receipt of transplant; death was considered a competing risk. The Fine‐Gray method was performed to determine whether PEth testing affected risk of evaluation termination/ delisting due to alcohol use. Results: Three hundred and seventy‐five patients with alcohol‐related indications for transplant (157 in 2017; 210 in 2019) were included. The final IPW‐adjusted model for the composite outcome of terminations/delisting due to alcohol use retained two significant variables ( P < .05): PEth era and BMI category. Patients evaluated during the PEth era were almost three times more likely to experience an alcohol‐related termination/delisting than those in the pre‐PEth era (sHR = 2.86; 95%CI 1.67–4.97) Conclusion: We found that availability of PEth testing at our institution was associated with a higher rate of exclusion of patients from eligibility for liver transplant. Use of PEth testing has significant potential to inform decisions regarding transplant candidacy for patients with alcohol‐related liver disease.